Efisiensi Diri Dan Penggunaan Sistem ERP: Peran Mediasi Persepsi Yang Berguna Dan Persepsi Mudah Digunakan - Amandasari, Gaby (E-Jurnal Akuntansi, 2019)
The purpose of this study is to find out how the implementation of ERP in companies affected by self-efficacy employees, as well as the perceived usefulness and perceived ease of use of ERP system. The data were obtained from 70 questionnaires distributed to employess of ERP system users who work in PT. Pembangunan Perumahan (Persero) Tbk, which is one of the companies of ERP users in Indonesia. Inferential statistical analysis used in Structural Equation Model (SEM) with Partial Least Square (PLS) approach. The result of this study shows that ERP system self-efficacy significantly positive affect on ERP system usage mediated by perceived usefulness and perceived ease of use. Keywords : Self-Efficacy; ERP System Usage; Perceived Usefulness; Perceived Ease Of Use.